LEGAL FRAMEWORK FOR CORPORATE AND GOVERNMENT PARADIGM TO DISASTER VICTIMS - Sulaksono (jfpublisher, 2023)
The environmental law enforcement paradigm has not implimented well. This can be known through the government's inability to stop several acts of environmental destruction committed by several corporations. On the other hand, based on the principles of environmental law, it is stated that the government must be responsible for environmental management. The topic of this research is important to uncover the background between whether or not there were violations of regulations committed by corporations. The results of the research indicated that the paradigm of enforcing environmental law is contained in Law No. 32/2009 concerning Environmental Protection and Management; Law No. 24/2007 concerning Disaster Protection; Law No. 30/1999 concerning AAPS (Arbitration and Alternative Dispute Resolution) and Law No. 4/2009 concerning Mining is still a normative paradigm which causes the weakening of environmental law enforcement.